Drosophila Sirtuin 6 mediates developmental diet-dependent programming of adult physiology and survival. - Shukla, N.; Kolthur-Seetharam, U. (Aging Cell, 2022)
Organisms in the wild experience unpredictable and diverse food availability throughout their lifespan. Over-/under-nutrition during development and in adulthood is known to dictate organismal survival and fitness. Studies using model systems have also established long-term effects of developmental dietary alterations on life-history traits. However, the underlining genetic/molecular factors, which differentially couple nutrient inputs during development with fitness later in life are far less understood. Using Drosophila and loss/gain of function perturbations, our serendipitous findings demonstrate an essential role of Sirtuin 6 in regulating larval developmental kinetics, in a nutrient-dependent manner. The absence of Sirt6 affected ecdysone and insulin signalling and led to accelerated larval development. Moreover, varying dietary glucose and yeast during larval stages resulted in enhanced susceptibility to metabolic and oxidative stress in adults. We also demonstrate an evolutionarily conserved role for Sirt6 in regulating physiological homeostasis, physical activity and organismal lifespan, known only in mammals until now. Our results highlight gene-diet interactions that dictate thresholding of nutrient inputs and physiological plasticity, operative across development and adulthood. In summary, besides showing its role in invertebrate ageing, our study also identifies Sirt6 as a key factor that programs macronutrient-dependent life-history traits.